Encyclopedia of Automotive Engineering 2014
DOI: 10.1002/9781118354179.auto121
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Compression‐Ignition Combustion for High Efficiency and Ultra‐LowNOXand Soot

Abstract: Low temperature combustion of gasoline or gasoline‐like fuels has significant advantages over conventional piston‐engine combustion processes. This combustion process, which is based on the compression‐ignition (CI) of a premixed or partially premixed dilute charge, is capable of achieving thermal efficiencies at or above those of diesel engines, engine‐out NO X and soot emissions well below mandated standards, and loads as high as those typical of turbo‐char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 146 publications
0
15
0
Order By: Relevance
“…In previous studies [21,71] , it was found that as the degree of thermal inhomogeneity of the fuel/air charge increases at the on- set of the main combustion, the overall combustion is more likely to occur by the deflagration mode of combustion, which in turn reduces the peak HRR by slowing down the overall combustion process and prolonging the combustion duration. In addition, it was also found that the negatively-correlated T − φ distribution in the mixture has an adverse effect on the HCCI combustion because the evaporation cooling effect of direct fuel injection offsets that of mixture inhomogeneity by narrowing the differences in the ignition delays of local fuel/air mixtures with different reactivity, consequently leading to a shorter combustion duration and an excessive HRR [23,33,38,[71][72][73] . Recently, Bansal et al [38] demonstrated that the HCCI combustion with compression heating is more apt to occur by the spontaneous ignition mode than that under constant volume because the compression heating tends to reduce temperature gradients before the main combustion.…”
Section: Combustion Mode Analysismentioning
confidence: 97%
“…In previous studies [21,71] , it was found that as the degree of thermal inhomogeneity of the fuel/air charge increases at the on- set of the main combustion, the overall combustion is more likely to occur by the deflagration mode of combustion, which in turn reduces the peak HRR by slowing down the overall combustion process and prolonging the combustion duration. In addition, it was also found that the negatively-correlated T − φ distribution in the mixture has an adverse effect on the HCCI combustion because the evaporation cooling effect of direct fuel injection offsets that of mixture inhomogeneity by narrowing the differences in the ignition delays of local fuel/air mixtures with different reactivity, consequently leading to a shorter combustion duration and an excessive HRR [23,33,38,[71][72][73] . Recently, Bansal et al [38] demonstrated that the HCCI combustion with compression heating is more apt to occur by the spontaneous ignition mode than that under constant volume because the compression heating tends to reduce temperature gradients before the main combustion.…”
Section: Combustion Mode Analysismentioning
confidence: 97%
“…Subsequent direct injections occur during the compression stroke to create slight levels of fuel stratification in an attempt to create sequential autoignition events while maintaining ultra-low NOx and soot emissions. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] MFS increases the stratification level by reducing to the amount of premixed fuel and typically features all direct injections during the compression stroke. In addition, MFS strategies typically feature a fuel injection event near top dead center (TDC) of the compression stroke to trigger combustion.…”
Section: Fuel Stratification Levels For Ltgcimentioning
confidence: 99%
“…Advanced low-temperature-combustion (LTC) strategies of downsized and boosted engines are capable of offering ultra-low emissions and higher efficiencies [2][3][4]. In these engines, combustion is chemically driven by the autoignition process with no direct means to control the ignition timing and combustion rate.…”
Section: Introductionmentioning
confidence: 99%